Value Preferences and Intergenerational Differences of Tourists to Traditional Chinese Villages - Wei Qi; Lin Li; Jie Zhong (Discrete Dynamics in Nature and Society)
Tourist values determine the behavior of tourists. To pinpoint the behaviors and preferences of tourists, it is necessary to explore their value orientation and intergenerational differences. The exploration is of great significance to the activation of tourism in traditional villages. After analyzing the value of tourists to two traditional villages (Hongcun and Xidi), this paper investigated the value preferences and intergenerational differences of tourists of four generations to traditional villages, using means-end chain (MEC) theory and hard laddering. Through a questionnaire survey on tourists born in the 1960s, 1970s, 1980s, and 1990s, the authors established 36 MEC value chains of 18 classes. The results show that the post-60s traditional village tourists are a generation of wisdom-loving learners, who prefer the values of wisdom and self-improvement; the post-70s and 80s tourists are a generation of beauty lovers with a strong sense of belonging, who prefer the values of beautiful world, inner harmony, and sense of belonging; the post-90s tourists are a generation of inclusive advocators of diversity, with no special value preference. These results provide theoretical support and practical enlightenment for the market segmentation of traditional village tourism and the protection and activation of traditional villages.